Metabolomics survey of uropathogenic bacteria in human urine - Chan, Carly C. Y.; Groves, Ryan A.; Rydzak, Thomas; Lewis, Ian A. (Frontiers in Microbiology, 2024)
IntroductionUrinary tract infections (UTIs) are one of the most prevalent infections in North America and are caused by a diverse range of bacterial species. Although uropathogenesis has been studied extensively in the context of macromolecular interactions, the degree to which metabolism may contribute to infection is unclear. Currently, most of what is known about the metabolic capacity of uropathogens has been derived from genomics, genetic knockout studies or transcriptomic analyses. However, there are currently very little empirical data on the metabolic activity of uropathogens when grown in urine.MethodsTo address this gap, we conducted a systematic survey of the metabolic activities of eight of the most common uropathogenic bacterial species that collectively represent 99% of uncomplicated UTIs.ResultsLiquid chromatography-mass spectrometry (LC–MS) analyses of human urine cultures revealed that uropathogens have four distinct metabolic clades. We generalized these clades as serine consumers (Escherichia coli, Klebsiella pneumoniae, and Proteus mirabilis), glutamine consumers (Pseudomonas aeruginosa), amino acid abstainers (Enterococcus faecalis and Streptococcus agalactiae), and amino acid minimalists (Staphylococcus aureus and Staphylococcus saprophyticus). These metabolic classifications can be further subdivided on a species-to-species level.DiscussionThis survey provides a framework to understanding the metabolic activity of the diverse range of uropathogens and how these species use divergent metabolic strategies to occupy the same niche.